Biomechanical assessment of patellar tendon advancement in patients with cerebral palsy and crouch gait - Karabulut, Derya; Arslan, Yunus Ziya; Salami, Firooz; Wolf, Sebastian Immanuel; Götze, Marco (The knee, 2021)
Background - Patellar height is a valuable measure to evaluate the effect of patellar tendon advancement (PTA) on knee function. In the literature, there is no validated procedure to measure the patellar height. In this study we aimed to (1) determine the patella position through musculoskeletal modeling, (2) investigate the effects of two surgical procedures applied for PTA, and (3) assess the effect of PTA in combination with single-event multilevel surgery (SEMLS) on the knee kinematics of patients with cerebral palsy (CP) and crouch gait. - Method - Three-dimensional gait and X-ray data of children with CP and crouch gait were retrospectively analyzed if they had received a SEMLS in combination with PTA (PTA group, n = 18) or without PTA (NoPTA group, n = 18). A computational musculoskeletal model was used to quantify patella position, knee extension moment arm, and knee kinematics pre- and postoperatively. - Results - Patellar height significantly decreased in the PTA group (P = 0.004), while there was no difference in the NoPTA group (P > 0.05). The bony procedure for PTA provided a better Insall-Salvati ratio than the soft tissue procedure. The peak knee extension moment arm significantly increased in the PTA group (P = 0.008). In terms of postoperative knee joint kinematics, the PTA group was closer to typically developed children than the NoPTA group. - Conclusion - Musculoskeletal modeling was found to be an effective tool for the determination of the patellar height. PTA improved the patella position, knee extension moment arm, and knee kinematics and was an effective procedure for the surgical management of crouch gait in patients with CP.
Gesehen am 17.11.2021